Konsep Deep Learning dalam Perspektif Filsafat Ki Hadjar Dewantara - Putri, Marsha Amelia; Dya Qurotul A'yun (JPUS: Jurnal Pendidikan Untuk Semua, 2025)
This research aims to explore the integration of the concept of deep learning in the perspective of Ki Hadjar Dewantara's educational philosophy. The method used is descriptive qualitative through literature study. This research found that the concept of deep learning, which focuses on deep understanding, critical reflection, and practical application, has alignment with Ki Hadjar Dewantara's educational principles, such as freedom of learning, personalization of education, and character building. This integration not only improves students' intellectual abilities but also forms a personality with character and competence. In addition, the use of technology in deep learning opens up opportunities for personalization of learning and the application of local values that are relevant in the era of globalization.